Gun policy in the United States and Canada : the impact of mass murders and assassinations on gun control - Fleming, Anthony K. (Continuum, 2012)
"The shooting at Virginia Tech in 2007 was one of the worst mass murders in the U.S., but it did not lead to any new federal gun control policy. In contrast, following a similar event in Montreal in 1989, Canada created new comprehensive gun policy. Such different outcomes are the focus of this survey, which sets out to explore the gun policymaking process in the U.S. and Canada in the aftermath of major events. It explores the many factors that lead to the drastically different reactions of the federal governments in each state if the aftermath of a mass shooting or assassination. To do so, it examines such elements as institutional arrangements, interest groups pressures (NRA, e.g.), and the party in power, studying the impact of such key events as the assassinations of J.F. Kennedy, Martin Luther King, Jr., Georgina Leimonis and shootings that occurred at Columbine, Stockton, and Vernon. A unique comparative study, Gun Policy in the United States and Canada will be an essential resource to anyone researching gun policy issues and comparative policymaking"--Provided by publisher.